The Effect of Attractiveness of Creative Product and Entrepreneurship Subjects through Creativity on Entrepreneurial Interest - Suci, Hestri Candra; Hermawati, Sri (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Entrepreneurial activities today are accessible to every class of society, many students have done entrepreneurship, especially at the vocational high school level. Students interest in entrepreneurship activities can be influenced by internal factors and external factors. The initial hypothesis of the study found that there were external factors originating from teaching and learning activities, which focused on the interaction of teachers and students. This study aims to determine how much influence this learning has on the creative power and entrepreneurial interest of public and private vocational school students in Bekasi city. The population in this study included all Vocational High School's students in Bekasi City using a purposive random sampling method, using a closed questionnaire technique with alternative answers using a Likert scale with a sample of 200 students from class XI and XII at public and private Vocational High Schools in Bekasi City who participated in the activity of learning to teach on creative product subjects and entrepreneurship. Data collection was carried out for 1 month at the beginning of the school year. The research was analyzed using path analysis, emphasizing the causal relationship between variables, namely creative and entrepreneurial product subjects on students' creativity and business interests. The results showed that the attractiveness of creative product subjects had a direct influence on student creativity by 20.3%, and a direct effect on student entrepreneurial interest by 30.5%.